KONSTRUKSI GENDER DALAM BUKU AJAR MUATAN LOKAL BAHASA MADURA Studi Isu Gender Dalam Bahasa Madura - Iqbal Nurul Azhar (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2009)
Madurese culture that puts the position of man higher than woman sometimes results stereotype. This stereotype states that many gender imbalances exist in Madurese communities not only in family or in social relationships, but also in educationan. To prove this storeotype, a research focussing on Madurese Language handbooks used in elementary school was conducted. Three books were analyzed using linguistcs approach. The result of the study gives an evidance that the gender imbalence do exist in this field.